The Contrasting Role of Single-cell Studies in the Theoretical Debate on Determinism in Molecular Biology - Heams, Thomas (Organisms. Journal of Biological Sciences, 2023)
In experimental biology, the last three decades have seen a flood of techniques dedicated to study biological phenomena at the single-cell level, and this article aims to reflect on how these technical advances can contribute to the renewal of theoretical perspectives in biology. The case studied here is that of the critique of the genetic determinism of molecular biology. The demonstration of unpredictability in gene expression at the single-cell level, a phenomenon known as stochastic gene expression, even in clonal populations, initially appeared to be a decisive indication that cells do not actually behave as predicted by deterministic frameworks. However, single-cell techniques have also revealed other sources of genetic variation that nuance this picture. The role of single-cell studies thus appears contrasted, and can be used to support or challenge the paradigm of genetic determinism (GDP). This opens up a more general debate on the practical ability of molecular biologists to criticize their own paradigms.